2018
DOI: 10.1007/s12565-018-0453-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of somatostatin-28 (1-12), calcitonin gene-related peptide, and substance P in the squirrel monkey brainstem: an immunocytochemical study

Abstract: Using an immunocytochemical technique, we have studied the distribution of fibers and cell bodies containing somatostatin-28 (1-12) [SOM-28 (1-12)], calcitonin gene-related peptide (CGRP), and substance P (SP) in the brainstem of Saimiri sciureus. The distribution of the peptidergic cell bodies was very restricted: perikarya containing SOM-28 (1-12) were only observed in the substantia grisea centralis, while no immunoreactive cell bodies containing CGRP or SP were visualized. Fibers containing SOM-28 (1-12), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…SP, mainly via the neurokinin-1 receptor, plays many functional/pathophysiological roles in inflammation-associated vasodilation, pain perception, immune responses, learning, nausea, stress, anxiety, cancer and depression [3,4]. SP is widely distributed through the nervous system (e.g., thalamus, hypothalamus, brainstem, spinal cord) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP, mainly via the neurokinin-1 receptor, plays many functional/pathophysiological roles in inflammation-associated vasodilation, pain perception, immune responses, learning, nausea, stress, anxiety, cancer and depression [3,4]. SP is widely distributed through the nervous system (e.g., thalamus, hypothalamus, brainstem, spinal cord) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Alpacas can live from the sea level to 5,000 m altitude, indicating that this species has special physiological adjustment mechanisms, as are those related to providing sufficient blood flow to the brain and the implication of these unique features in the neuroanatomical organization of some CNS nuclei. In addition to those works focused on the alpaca reproductive mechanisms, several studies have been previously performed on the neuroanatomical location of neuropeptides (calcitonin gene-related peptide, somatostatin-28 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), neurotensin, leucine-enkephalin, alphaneo-endorphin, adrenocorticotropic hormone (18-39), beta-endorphin ) in the alpaca brainstem [17][18][19][20][21][22]. In addition, a recent study has shown a close neuroanatomical relationship between the enkephalinergic (methionine-enkephalin) and tachykininergic (substance P) systems in the alpaca diencephalon and the presence of some neuropeptides (e.g., neurotensin) has also been reported in this region of the alpaca CNS [5,23].…”
Section: Introductionmentioning
confidence: 99%